Translation-optimized Memory Compression for Capacity - Panwar, Gagandeep; Laghari, Muhammad; Bears, D.; Liu, Yuqing; Jearls, Chandler; Choukse, Esha; Cameron, K.; Butt, A.; Jian, Xun; Choukse, Esha (2022 55th IEEE/ACM International Symposium on Microarchitecture (MICRO), 2022)
The demand for memory is ever increasing. Many prior works have explored hardware memory compression to increase effective memory capacity. However, prior works compress and pack/migrate data at a small - memory block-level - granularity; this introduces an additional block-level translation after the page-level virtual address translation. In general, the smaller the granularity of address translation, the higher the translation overhead. As such, this additional block-level translation exacerbates the well-known address translation problem for large and/or irregular workloads. A promising solution is to only save memory from cold (i.e., less recently accessed) pages without saving memory from hot (i.e., more recently accessed) pages (e.g., keep the hot pages uncompressed); this avoids block-level translation overhead for hot pages. However, it still faces two challenges. First, after a compressed cold page becomes hot again, migrating the page to a full 4KB DRAM location still adds another level (albeit page-level, instead of block-level) of translation on top of existing virtual address translation. Second, only compressing cold data require compressing them very aggressively to achieve high overall memory savings; decompressing very aggressively compressed data is very slow (e.g., 800 ns assuming the latest Deflate ASIC in industry). This paper presents Translation-optimized Memory Compression for Capacity (TMCC) to tackle the two challenges above. To address the first challenge, we propose compressing page table blocks in hardware to opportunistically embed compression translations into them in a software-transparent manner to effectively prefetch compression translations during a page walk, instead of serially fetching them after the walk. To address the second challenge, we perform a large design space exploration across many hardware configurations and diverse workloads to derive and implement in HDL an ASIC Deflate that is specialized for memory; for memory pages, it is 4X as fast as the state-of-the art ASIC Deflate, with little to no sacrifice in compression ratio. Our evaluations show that for large and/or irregular workloads, TMCC can either improve performance by 14% without sacrificing effective capacity or provide 2.2x the effective capacity without sacrificing performance compared to a state-of-the-art hardware memory compression for capacity.